Biotechnological Approach Based on Selected Saccharomyces cerevisiae Starters for Reducing the Use of Sulfur Dioxide in Wine - Capece, Angela (Microorganisms, 2020)
Sulfites are considered the main additives in winemaking for their antimicrobial, antioxidant and anti-oxidasic activities. The current concern about the potential negative effects of sulfur dioxide (SO(2)) on consumer health has focused the interest on replacing or reducing SO(2) use. Our work aims to develop a strategy based on the use of selected starter culture, able to perform wine fermentation without SO(2) addition. Four selected Saccharomyces cerevisiae indigenous strains were tested as mixed starter cultures in laboratory scale fermentations. The starter culture, characterized by a similar percentage of dominance of both strains composing the mixed starter and able to produce a wine characterized by the best combination of chemical and aromatic characteristics, was chosen. This mixed culture was tested as a starter at pilot scale with and without SO(2) addition, by using a higher inoculum level in the vinification without SO(2). The selected starter confirmed higher dominance ability in vinification without SO(2) addition than in SO(2)-added fermentation, demonstrating that sulfite addition is not a guarantee to reach an absolute dominance of starter culture on indigenous microflora. The proposed biotechnological tool allowed to produce good quality wines possessing also “functional properties”, as NO-SO(2) added wines were characterized by high polyphenol content and antioxidant activity.